(untitled) (Bulletin KNOB, 1994)
The so-called ’Bergportaal’ (janua montis), situated on the south-west side of the nave of the church of St Servatius in Maastricht comprises an elaborate Gothic portal preceded by a decorated porch. The portal consists of a tympanum and lintel showing the death and triumph of the Virgin Mary, framed by alternately figurative and foliate archivolts supported by eight large statues. In previous centuries the Bergportaal was extensively restored. Missing parts were replaced and the sculpture disappeared under a thick and coarse coating of paint and piaster, which probably accounts for the rather low esteem in which the portal has generally been held. During restoration work in 1992 these layers were removed from three of the better-preserved archivolt statuettes, an operation which shed new light on the quality of the ensemble and on its original polychromy. It became clear that the sculpture was not the result of a single, continuous campaign. Apparently an early Gothic portal erected circa 1170-80 had been enlarged shortly after 1200. The earliest sculpture is of very high quality and bears a marked resemblance to Meuse-valley metalwork of the same period. This indicates that Meuse-valley sculpture did not lag behind the other arts in the region, as is generally held, and that stylistically the Bergportaal has little to do with the portal of Senlis (circa l170) in northern France, with which it is usually - rather unfavourably - compared. Rather than being a late and provincial thirteenth-century copy of this portal, the earliest sculpture of the Bergportaal is probably more or less contemporary with it, and this - in view of the similarities - suggests a common prototype, probably somewhere in northern France or present-day Belgium. Unfortunately, much of the architecture and sculpture there has not survived, but scarce fragments in Picardie, Artois, Hainault and in the Meuse Valley itself show that, when built, the Bergportaal was not the lonely northern freak it is today. In fact, as the most substantial remnant of this northern output, the Bergportaal bears testimony to the important, but rather underestimated role played by the ’north’ in the development of Gothic sculpture in the last quarter of the twelfth century.